Anti-inflammatory management for tendon injuries - friends or foes? - Chan Kai-Ming; Fu Sai-Chuen (BMC, 2009)
Abstract Acute and chronic tendon injuries are very common among athletes and in sedentary population. Most physicians prescribe anti-inflammatory managements to relieve the worst symptoms of swelling and pain, including non-steroidal anti-inflammatory drugs, corticosteroids and physical therapies. However, experimental research shows that pro-inflammatory mediators such as prostaglandins may play important regulatory roles in tendon healing. Noticeably nearly all cases of chronic tendon injuries we treat as specialists have received non-steroidal anti-inflammatory drugs by their physician, suggesting that there might be a potential interaction in some of these cases turning a mild inflammatory tendon injury into chronic tendinopathy in predisposed individuals. We are aware of the fact that non-steroidal anti-inflammatory drugs and corticosteroids may well have a positive effect on the pain control in the clinical situation whilst negatively affect the structural healing. It follows that a comprehensive evaluation of anti-inflammatory management for tendon injuries is needed and any such data would have profound clinical and health economic importance.